Pengaruh Kualitas dan Harga Produk Terhadap Minat Beli Salah Satu Produk Kecantikan di Indonesia - Adinda Puspitasari; Eki Wijayanti Putri; Sharon Nathaniela Badia Hutapea; Ahmad Gunawan (LP3M Universitas Putra Bangsa, 2022)
This study aims to examine, identify, and explain: 1) the effect of product quality on buying intention, 2) the effect of product price on buying intention, and 3) the effect of product quality and price on buying interest. The design of this research is quantitative research which is a research survey using statistical analysis methods. The test results show that product quality (X1) with t count (24,648) > t table (1,984), price (X2) with t count (15,478) > t table (1,984). It can be said that the product quality variable has a significant effect on consumer buying intention, and the price variable has a significant effect on consumer buying interest. The obtained value of Fcount (521.660) > Ftable (3.090) and a significant value (Sig.) less than 0.05 (0.000 < 0.05). This means that the hypothesis which states that there is a significant influence between product quality and the price of consumer buying intention can be accepted.